UNDERSTANDING THE CAUSES AND IMPACT OF CIGARETTES ADDICTION AMONG TEENS - Anggraini, Shintia; Elmy Antika , Rini; Rahma Wahyuningsih , Rany; Nurhaliza , Shinta; Adventus; Okta Sari , Resti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study discusses the factors causing and the impact of cigarette addiction among students. Using a literature study method on 25 journals from 2015-2024, this study identified the main causal factors, including peer influence, social environment, family, curiosity, lack of knowledge, and easy access to cigarettes. The impacts include health, economic, psychological, and social problems, such as decreased academic achievement and financial pressure. This study also found that dominant factors such as cigarette advertising, permissive parenting, and low emotional intelligence contributed to worsening the condition of addiction. Interventions through education, restrictions on access to cigarettes, and regulation of tobacco advertising are needed to reduce the prevalence of smoking among students. Thel results ofl this studyl provide importantl insights forl educators, parents, andl policy makers tol design effective prevention strategies to protect the younger generation from the dangers of cigarettes.